2018
DOI: 10.4236/gsc.2018.82015
|View full text |Cite
|
Sign up to set email alerts
|

Green Bio-Based CaO from Guinea Fowl Eggshells

Abstract: Eggshells are among the emerging hazardous waste from the food processing industry. This work sought to valorize waste guinea fowl eggshells. Guinea fowl eggshells (GFEs) were evaluated in the production of CaO for chemical and industrial application. The functionality, thermal stability, elemental composition, phase distribution and surface morphology properties of uncalcined GFEs and GFEs calcined at 700˚C, 800˚C, 900˚C, 1000˚C and 1100˚C were systematically studied by FTIR, TGA, XRF, XRD and SEM-EDX respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Referring to Fig. 1, a minor weight loss (~5 wt.%) at temperature of < 300°C is attributed to the loss of moisture and volatile organic substance, while a significant decomposition (~40 wt.%) at the temperature of >650°C is attributed to the CaCO3 conversion to CaO [11][12][13]. Salauddeen et al [14] reported that the CO2 release is taken from the point where a significant weight loss is observed till the end of analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to Fig. 1, a minor weight loss (~5 wt.%) at temperature of < 300°C is attributed to the loss of moisture and volatile organic substance, while a significant decomposition (~40 wt.%) at the temperature of >650°C is attributed to the CaCO3 conversion to CaO [11][12][13]. Salauddeen et al [14] reported that the CO2 release is taken from the point where a significant weight loss is observed till the end of analysis.…”
Section: Resultsmentioning
confidence: 99%
“…8 (continued) potentially increase the environmental impact. This could be mitigated by using lime from waste sources, for instance carbide lime [54] or eggshells [55].…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, about 250,000 tons of eggshell waste is released annually (Faridi and Arabhosseini 2018). Waste egg shells are among useful agricultural biowaste materials that have the following properties; they are biodegradable, recyclable and biocompatible (Pedavoah et al, 2018). Egg shells are mainly composed of calcium carbonate (CaCO3), which accounts for about 93.6% by weight, followed by calcium triphosphate (0.8%), which accounts for about 10% of a hen's egg (Neunzehn, Szuwart, and Wiesmann 2015).…”
Section: Introductionmentioning
confidence: 99%